Mechanically robust biomass-derived carbonaceous foam for efficient solar water evaporation. (4th November 2022) - Ma, Sainan; Wu, Yuhao; Lv, Ruiling; Gao, Xiang; Wang, Qianqian
Abstract : The biomass-derived carbonaceous foam with excellent mechanical strength and evaporation efficiency has promising potential for practical interfacial solar water treatment. Abstract : Interfacial solar water evaporation is a sustainable and energy-saving water treatment technology to tackle the freshwater shortage issue. Low-cost, durable, and highly efficient photothermal materials play a crucial role in practical solar water evaporation. Here, banana is chosen as the raw material for solar water evaporation mainly due to its high yield and renewability. The carbonized banana foam (CBF) with interconnected porous structure ensures ultra-fast water supply and high solar absorption ability. The CBF-based system with a 3D structure possesses a high solar water evaporation rate of 1.51 kg m −2 h −1 and an energy conversion efficiency of 93.3% under 1 sun illumination. Notably, this banana-derived CBF presents robust mechanical strength that ensures long-term solar water evaporation, surpassing most fragile carbonized biomass materials. Furthermore, the CBF exhibits excellent water treatment performance, including seawater desalination and wastewater purification. This work provides new inspiration to develop simple, cost-effective, and green photothermal materials for applicable solar water treatment.